2023
DOI: 10.21554/hrr.042306
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Analysis of Mortality in Bosnia and Herzegovina: A Preliminary Analysis

Abstract: In this study, using the methods of spatial autocorrelation in geographic information systems (GIS), an analysis of the spatial distribution of mortality rates in Bosnia and Herzegovina was performed in order to identify high-risk areas with increased mortality and depopulation. Spatial analysis is based on the calculation of global (Global Moran’s I and Getis-Ord General G) and local (Anselin Local Moran’s I and Getis-Ord Gi*) statistical indices of spatial autocorrelation. The values of global statistical in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…For instance, these factors contributed to negative natural population changes and the emigration of young people (mainly between 20 and 40 years old). Consequently, these processes led to a decrease in the population's potential biodynamics and vitality (Kadusic et al, 2023) (BHAS, FZS, RZSRS, 2022) are significantly correlated. The study's findings demonstrated that the vital index and the components of natural population change, as well as the ageing index and the ageing coefficient, are strongly correlated.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, these factors contributed to negative natural population changes and the emigration of young people (mainly between 20 and 40 years old). Consequently, these processes led to a decrease in the population's potential biodynamics and vitality (Kadusic et al, 2023) (BHAS, FZS, RZSRS, 2022) are significantly correlated. The study's findings demonstrated that the vital index and the components of natural population change, as well as the ageing index and the ageing coefficient, are strongly correlated.…”
Section: Discussionmentioning
confidence: 99%